An investigation into the effect of the application of sub sonic vibrations during the period of solidification of castings with particular reference to a material for gas turbine blades - 'H.R. Crown Max' - Hinchcliff, S. (College of Aeronautics, Cranfield, 1955)
The report considers the theoretical relations between microstructures of castings and their mechanical properties and the effects and advantages of vibration during solidification; the design of a melting furnace and a mechanical vibrator to be used together, and the use of sillimanite bonded with Ethyl Silicate as a material for moulds to withstand vibration.